Survey of traditional wind catchers of the middle east - Valipour, Ehsan; Oshrieh, Rouhollah (My University, 2013)
Natural phenomena and environmental have important role about culture economic and social infrastructures. The Iranian's buildings in the desert are difference with the other regions, because the climate of desert is so different. Because of there was not a modern technology for a long times. The architects were forced to solve their problems with natural conditions. In the past, without new technology just some sagacious architecture ways can help in hard condition like summer. Badgir or wind catcher is an old technology that with it, the interior space became cooler. The function of wind catcher depends on the condition of wind catcher sun radiation in the area. In the past time and in historical buildings in hot and dry area, the wind tower functioned similar the modern air- conditioner. Material of wind catcher is so important because of high swing of temperature is difference between day and night in this area. They made wind catcher with mud brick and it save the heat of sun during the day and reflected it to environment during the night. © 2013 American Society of Civil Engineers.
2nd Annual International Conference Sustainable Design, Engineering and Construction, ICSDEC 2012 --
Keywords: cooling system; sustainable architecture; wind catcher